Måleegenskaper ved den norske versjonen av Aberrant Behavior Checklist (ABC) - Halvorsen, Marianne; Myrbakk, Even; Martinussen, Monica (Regionsenter for barn og unges psykiske helse (RBUP), 2015)
Description. The Aberrant Behavior Checklist (ABC) is suitable for individuals with an intellectual disability and was developed by Aman and Singh in 1986. The latest ABC-version (Community) was published in 1994, and translated (and back translated) to Norwegian by the Mapi Research Institute. The copyright ownership is held by Slosson Educational Publications Inc. The ABC is a 58-item checklist grouped into five subscales. It is a proxy measure requiring good knowledge of the index person. It takes less than 15 minutes to complete. Researchers and clinicians can administer and interpret the checklist. Literature search. A systematic review of studies on the psychometric properties of the Norwegian, Swedish and Danish versions of the ABC identified 262 articles, in which three, all Norwegians, were finally included. The articles included covered individuals with intellectual disabilities from adolescents to adulthood. Two of the articles included participants from the county of Nordland in which a substantial portion also were patients in the specialized health care services. A smaller study reported population based data from the county of Trøndelag. Psychometrics. Construct validity was indicated by a good correspondence between the ABC and appropriate measures of general psychopathology. The scales had good to excellent internal consistency. Data regarding inter-rater agreement was sparse and preliminary, however indicating adequate correspondence for three out of five of the subscales. Conclusion. There are no Norwegian norms available. The validity of the ABC is not sufficiently examined, but existing data indicate a substantial overlap with measures of general psychopathology. The scales have good to excellent internal consistency. Beskrivelse. Aberrant Behavior Checklist (ABC) er et spørreskjema som brukes for å kartlegge atferdsproblemer hos barn, ungdom og voksne med utviklingshemning. I den amerikanske manualen er det normer for alderen 6 til 89 år. ABC ble utviklet av Aman og Singh i 1986. Den ...